Curcumin promotes exosomes/microvesicles secretion that attenuates lysosomal cholesterol traffic impairment. Issue 4 (29th November 2013) - Canfrán‐Duque, Alberto; Pastor, Óscar; Quintana‐Portillo, Rocío; Lerma, Milagros; de la, Gema; Martín‐Hidalgo, Antonia; Fernández‐Hernando, Carlos; Lasunción, Miguel A.; Busto, Rebeca
<x xml:space="preserve">Abstract</x> Scope Exosomes/microvesicles are originated from multivesicular bodies that allow the secretion of endolysosome components out of the cell. In the present work, we investigated the effects of curcumin, a polyphenol, on exosomes/microvesicles secretion in different cells lines, using U18666A as a model of intracellular cholesterol trafficking impairment. Methods and results In both HepG2 hepatocarcinoma cells and THP‐1 differentiated macrophages, treatment with curcumin affected the size and the localization of endosome/lysosomes accumulated by U18666A, and reduced the cholesterol cell content. To ascertain the mechanism, we analyzed the incubation medium. Curcumin stimulated the release of cholesterol and the lysosomal β‐hexosaminidase enzyme, as well as the exosome markers, flotillin‐2 and CD63. Electron microscopy studies demonstrated the presence of small vesicles similar to exosomes/microvesicles in the secretion fluid. These vesicles harbored CD63 on their surface, indicative of their endolysosomal origin. These effects of curcumin were particularly intense in cells treated with U18666A. Conclusion These findings indicate that curcumin ameliorates the U18666A‐induced endolysosomal cholesterol accumulation by shuttling cholesterol and presumably other lipids out of the cell via exosomes/microvesicles secretion. This action may contribute to the potential of curcumin in the treatment of lysosomal storage diseases.